Male Hypogonadism and Obesity: An Insight - Muhammad Naeem, Shahid Shehzad, Rashed Ali Khan, Rasif Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Obesity, a clinical condition that is on the rise internationally and is highly associated to lower testosterone levels in males, is the most strongly linked clinical condition. In addition to this, it is one of the most reliable signs that a guy may require testosterone replacement medication. When it comes to obesity, the severity of the condition can determine whether the hypothalamic-pituitary-testicular axis (HPT) is suppressed. Moderate obesity, on the other hand, is typically characterized by lower levels of sex hormone binding globulin. Even though there is a connection in both directions between hypogonadism and obesity, the effect of adiposity on testosterone levels is much more significant than the impact that testosterone has on adiposity. The relationship between hypogonadism and obesity is complex and multifaceted. There are various components, both causal and correlative, on both sides of the contact, which can be thought of as a connection that goes in both directions. The number of people who are overweight or obese is increasing at an epidemic rate. In a manner quite like this, we have begun to observe a significant increase in the frequency of male hypogonadism. We are just now starting to get a better understanding of how these two ailments might interact with one another and make each other worse, as well as how treating one of these conditions can help in the treatment of the other.